Cutaneous adnexal carcinoma and the risk of SCC. (1st March 2019) - De Giorgi, V.; Salvati, L.; Barchielli, A.; Caldarella, A.; Gori, A.; Scarfì, F.; Savarese, I.; Pimpinelli, N.; Urso, C.; Massi, D.
Summary: Globally, skin cancer is one of most common forms of cancer. There are several types, the most common being non‐melanoma skin cancer, which includes basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). In the UK, more than 100, 000 new cases of non‐melanoma skin cancers are diagnosed every year. Cutaneous adnexal carcinomas (CACs) are rare tumors which are often difficult to diagnose. This study, from Italy, aimed to evaluate how the number of CACs in the population has changed over time and identify if there is a link between CAC presence and the risk of developing SCC. Data was analysed from the Tuscany Cancer Registry (TCR) from a 25‐year time period between 1985 and 2010. 242 patients with CACs were identified from this period with the number of patients with CACs growing from 2.5 per million in 1985‐87 to 19 per million in 2009‐10. Between 1997 and 2010, CAC presence in the population increased by 159%. It was also found that patients with CAC were 34 times more likely to develop SCC later in life than those without CAC, suggesting that this is a significant risk factor. The authors of this study predict that the number of patients with CAC is likely to continue to increase, due to an ageing population. This combined with the link between CAC and SCC highlights the need to improve diagnosis of CACs in the future.